EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL DALAM PEMBELAJARAN FIQIH DI MTs DARUSSALAM KUMALASA - Abd. Hadi Rohmani; Eka Vania Febriana (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Learning fiqh material has been delivered using conventional methods, namely lectures. This method leaves many problems, especially regarding learning effectiveness and student involvement. Therefore, a model that integrates technology into learning is needed, one of which is the use of audiovisual media. This media not only allows the delivery of information visually and auditorily but also offers opportunities to increase active student involvement through interesting and easy-to-understand material. So the use of audiovisual media can be a solution to overcome some of the shortcomings of the lecture method. This study focuses on 1) The learning process using audiovisuals at MTs Darussalam, and 2) The effectiveness of utilizing audiovisual media in teaching fiqh in class IX. This study uses a qualitative approach with a case study research design. The subjects of the study were fiqh teachers who used audiovisuals and 32 class IX students. Data collection was carried out through participatory observation, in-depth interviews, and documentation. This study found that 1) Learning by utilizing audiovisual media in fiqh learning in class IX MTs Darussalam Kumalasa has been implemented well. This can be seen from several aspects such as specific planning and selection of audiovisual video content that is relevant to the material being delivered. 2) The effectiveness of the use of audiovisual media in fiqh learning in class IX MTs Darussalam Kumalasa can be measured through various indicators, such as increased learning outcomes. This is reflected in the level of learning outcomes and student understanding that has increased, with a percentage of 27 students, or 84.37% having achieved KKM, from previously only 17 students,s or 57.12%. There are only 5 students or 15.63% who have not achieved KKM, from previously 15 students, ts or 46.88% who have not achieved KKM.